Emerging rurality in Malaysia: the adaptation of felda model - Mohamad Zainalabidin, Syahaneem; Djama, Marcel; Magrin, Geraud (Malaysian Palm Oil Board, 2023)
The Federal Land Development Authority (FELDA) model appears in many aspects to be a successful example of a rural development program in Malaysia. FELDA eventually rehabilitated more than 115 000 families of settlers in its active years of land opening. Together with its settlers, FELDA has managed to overcome significant challenges that came along over more than sixty years of its establishment. Yet today, the model appears fragile, and its future seems insecure. Upcoming vital issues and challenges threaten the sustainability of these settlement programmes in their endeavour to realise Malaysias rural development agenda. This article seeks to look at the emerging rurality in Malaysia and how the FELDA model is adapting to the settlers new demographic, social, and economic conditions, especially with the changing landscape of urbanisation, out-migration of the second and third generation of settlers and socio-economic conditions in Malaysia. This article also illuminates the issues and challenges faced by FELDA and its settlers and throws some light on the programme introduced by FELDA to develop its settlers social and economic qualities and related insights from both studies locations; FELDA Bukit Goh, Pahang and FELDA Tenggaroh, Johor. This article found that FELDA is currently facing a rural exodus where the next generation of settlers is exiting the scheme. The upward social mobility of the settlers children, especially in education, has led to their outmigration to the urban areas in the quest to find higher-paid employment. It is suggested that the adaptation programmes introduced in the model need to be mobilised to the fullest extent. It is not impossible to make the next generation committed to the programme as the community of FELDA has the advantage of being closely related to the management.